Nurse's perioperative care errors and related factors in the operating room. - Zabihirad, Jaber; Mojdeh, Soheila; Shahriari, Mohsen (Electronic Journal of General Medicine, 2019)
Introduction: Surgical cares are one of the most complex and costly health care services and optimizing them should be prioritized. Medical error as an adverse event can be considered as a threat to the safety of the patients. The revelation of errors is recognized as the basis for maintaining and improving the safety of patients; consequently, the present study aimed to investigate pre-, intra- and postoperative care errors in the operating rooms and their related factors. Method: This descriptive-analytic study was conducted in the operating rooms of selected hospitals of Isfahan University of Medical Sciences. The research instrument was a researcher-made questionnaire including demographic information, errors perioperative care and effective factors on these sorts of medical cares. Data were entered into SPSS software and analyzed by statistical tests. Findings: The mean error in the perioperative care was 25.33%, the highest error rate was related to preoperative care (31%) and then the error in postoperative care (25.24%) and the lowest level of error rate was seen in line with intraoperative care (20.75%); the results showed that the most effective factor in the occurrence of care errors in the operating room were environmental and structural factors (80.25%), then individual factors (75.27%) and management factors (61.75%). Conclusion: Regarding the lesser intraoperative cares error, it can be concluded that nurses are more focused on surgical procedures and surgical principles in line with the operation and are more likely to play a role of the assistant surgeon in the operating room and pay less attention to nursing care before and after the operation.